2022
DOI: 10.3389/fonc.2022.937114
|View full text |Cite
|
Sign up to set email alerts
|

Beyond N staging in colorectal cancer: Current approaches and future perspectives

Abstract: Traditionally, lymph node metastases (LNM) evaluation is essential to the staging of colon cancer patients according to the TNM (tumor–node–metastasis) system. However, in recent years evidence has accumulated regarding the role of emerging pathological features, which could significantly impact the prognosis of colorectal cancer patients. Lymph Node Ratio (LNR) and Log Odds of Positive Lymph Nodes (LODDS) have been shown to predict patients’ prognosis more accurately than traditional nodal staging and it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Upon microscopic observation of the pathological structure of both the RLN and TD, it was found that the TD possessed brous capsule and lacked any lymph node tissue. In contrast, the RLN was mainly composed of lymph node tissue (Arrichiello et al, 2022;Brouwer & Nagtegaal, 2021). Regional lymph node invasion, as the major metastasis pathway of colon cancer, played a decisive role in the postoperative staging of patients with colon cancer (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Upon microscopic observation of the pathological structure of both the RLN and TD, it was found that the TD possessed brous capsule and lacked any lymph node tissue. In contrast, the RLN was mainly composed of lymph node tissue (Arrichiello et al, 2022;Brouwer & Nagtegaal, 2021). Regional lymph node invasion, as the major metastasis pathway of colon cancer, played a decisive role in the postoperative staging of patients with colon cancer (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only relevant prognostic feature is the presence or absence of overt metastatic tumour cells within the LNs. However, this solely tumour centric system overlooks the role of immune and non-tumour compartment within the LNs 9 . This is critical, as no treatment strategy to date has reliably prevented the emergence of distant metastasis.…”
Section: Mainmentioning
confidence: 99%
“…Currently, the only relevant prognostic feature is the presence or absence of overt metastatic tumour cells within the LNs. However, this solely tumour centric system overlooks the role of immune and non‐tumour compartments within the LNs (Arrichiello et al., 2022). Understanding this process before distant metastasis formation is critical, as no treatment strategy to date has reliably prevented the emergence of distant metastasis.…”
Section: Introductionmentioning
confidence: 99%